(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The article is devoted to the factors that contributed to the formation of the language of a particular ethnic group and national character. The author notes that the language initially gives its speakers a certain picture of the world, and each given language – its own. Based on ethnolinguistic, linguodidactic, psycholinguistic and linguistic researches of the last decades, the author tries to show how the linguistic and always culturally colored picture of the world influences the person, forming his linguistic consciousness, nevertheless, cultural and national consciousness. The article emphasizes the importance of language and culture as important components not only of the individual linguistic personality, but also of the ethnos as a whole, where personality and ethnos are not opposed, but correlated, complementing each other. At the same time, according to the author, the knowledge possessed by the community of people determines the content of its mentality. It is noted that in the process of learning languages, an idea is formed about the foreign picture of the world, the ability to communicate harmoniously both in one’s own society and in other societies, to prevent and overcome conflicts caused by historical, political and religious differences of cultures, that is, creates an effective basis for establishing tolerant world. The paper presents analogies and comparisons of linguistic pictures of the world of various peoples. It is indicated that mutual recognition of them leads to a deeper recognition of oneself.